Phytolith Assemblages in Grasses Native to Central Argentina - Gallego, Lucrecia (2004)
Background and Aims Phytolith reference collections are a prerequisite for accurate interpretation of soil phytolith assemblages aimed at reconstructing past vegetation. In this study a phytolith reference collection has been developed for several grasses native to central Argentina: Poa ligularis, Piptochaetium napostaense, Stipa clarazii, Stipa tenuis, Stipa tenuissima, Stipa eriostachya, Stipa ambigua, Stipa brachychaeta, Pappophorum subbulbosum, Digitaria californica, Bothriochloa edwardsiana and Aristida subulata.